Skin-sparing mastectomy with immediate nipple reconstruction during autologous latissimus dorsi breast reconstruction: A review of patient satisfaction - Hurley, Ciaran M; McArdle, Adrian; Joyce, Kenneth M; O’Broin, Eoin (Archives of Plastic Surgery, 2018)
Background Nipple-areolar complex (NAC) reconstruction following curative mastectomy is traditionally performed as a second-stage procedure several months after initial breast reconstruction. The recent literature has documented the increasing popularity of immediate nipple reconstruction carried out simultaneously during autologous reconstruction. The aim of this study was to evaluate the surgical outcomes and patient satisfaction with immediate breast and nipple reconstruction performed in a single stage after skin-sparing mastectomy.Methods All patients who underwent a skin-sparing mastectomy with immediate latissimus dorsi flap breast and NAC reconstruction as a single-stage procedure from 2007 to 2015 were included. Patient demographics, oncologic details, and surgical outcomes were recorded. The BREAST-Q questionnaire was administered to patients to assess the impact and effectiveness of this reconstructive strategy.Results During the study period, 34 breast and NAC reconstructions in 29 patients were performed at Cork University Hospital. The majority of our patient cohort were non-smokers (93.1%) and did not receive adjuvant radiotherapy. Postoperative complications were infrequent, with no cases of partial necrosis or complete loss of the nipple. The response rate to the BREAST-Q was 62% (n=18). Patients reported high levels of satisfaction with the reconstructed breast (62±4), nipple reconstruction (61±4.8), overall outcome (74.3±5), and psychosocialwell-being (77.7±3.2).Conclusions Skin-sparing mastectomy with immediate nipple reconstruction during autologous latissimus dorsi reconstruction was demonstrated to be a safe and aesthetically reliable procedure in our cohort, yielding high levels of psychological and physical well-being. A single-stage procedure promotes psychosocial well-being involving issues that are intrinsically linked with breast cancer surgery.
Keywords: Breast; Surgery, plastic; Patient satisfaction; Reconstructive surgical procedures